Proposals for teaching practices in Biology: Biochemistry, Microbiology and Plant Biology - Souza, Patrick Gomes de; Rodrigues, Antonio Augusto Marques; Mendes, Joana Maia; Silva, Leidiane Pereira da; Castro, Márcia Seixas de (Brazilian Journal of Science, 2022)
The general objective of this work was to propose teaching practices in biological sciences for application in the classroom with high school students. Among the specific objectives were to carry out the theoretical basis of the proposed practices, list equipment and materials needed for the practices and describe the procedures in detail. Biology is present in our daily lives and many times we are not aware of this application. The subjects selected for the present study were: Biochemistry, Microbiology and Plant Biology. In biochemistry, the topic addressed was the evaluation of the enzymatic action on a substrate. This theme is related to the various applications of the use of enzymes, which can be done at an industrial, health or daily level. In the sphere of microbiology, topics on the fermentation of substrates through the action of microorganisms were addressed. Practice related to the production of foods such as beverages, cheeses and bakery. Finally, the theme of plant biology is being applied to develop knowledge about the environment, agriculture and gardening. Practices that can arouse entrepreneurship interests in students. Experimentation is an essential practice for the dissemination of scientific knowledge in the teaching of Science and Biology, it is an indispensable tool for scientific knowledge.